Candida Administration Worsens Uremia-Induced Gut Leakage in Bilateral Nephrectomy Mice, an Impact of Gut Fungi and Organismal Molecules in Uremia - Panpetch, Wimonrat (mSystems, 2021)
The impact of gut fungi and (1→3)-β-d-glucan (BG), a major fungal cell wall component, on uremia was explored by Candida albicans oral administration in bilateral nephrectomy (BiNx) mice because of the prominence of C. albicans in the human intestine but not in mice. As such, BiNx with Candida administration (BiNx-Candida) enhanced intestinal injury (colon cytokines and apoptosis), gut leakage (fluorescein isothiocyanate [FITC]-dextran assay, endotoxemia, serum BG, and bacteremia), systemic inflammation, and liver injury at 48 h postsurgery compared with non-Candida BiNx mice. Interestingly, uremia-induced enterocyte apoptosis was severe enough for gut translocation of viable bacteria, as indicated by culture positivity for bacteria in blood, mesenteric lymph nodes (MLNs), and other organs, which was more severe in BiNx-Candida than in non-Candida BiNx mice. Candida induced alterations in the gut microbiota of BiNx mice as indicated by (i) the higher fungal burdens in the feces of BiNx-Candida mice than in sham-Candida mice by culture methods and (ii) increased Bacteroides with decreased Firmicutes and reduced bacterial diversity in the feces of BiNx-Candida mice compared with non-Candida BiNx mice by fecal microbiome analysis. In addition, lipopolysaccharide plus BG (LPS+BG), compared with each molecule alone, induced high supernatant cytokine levels, which were enhanced by uremic mouse serum in both hepatocytes (HepG2 cells) and macrophages (RAW264.7 cells). Moreover, LPS+BG, but not each molecule alone, reduced the glycolysis capacity and mitochondrial function in HepG2 cells as determined by extracellular flux analysis. Additionally, a probiotic, Lactobacillus rhamnosus L34 (L34), attenuated disease severity only in BiNx-Candida mice but not in non-Candida BiNx mice, as indicated by liver injury and serum cytokines through the attenuation of gut leakage, the fecal abundance of fungi, and fecal bacterial diversity but not fecal Gram-negative bacteria. In conclusion, Candida enhanced BiNx severity through the worsening of gut leakage and microbiota alterations that resulted in bacteremia, endotoxemia, and glucanemia. IMPORTANCE The impact of fungi in the intestine on acute uremia was demonstrated by the oral administration of Candida albicans in mice with the removal of both kidneys. Because fungi in the mouse intestine are less abundant than in humans, a Candida-administered mouse model has more resemblance to patient conditions. Accordingly, acute uremia, without Candida, induced intestinal mucosal injury, which resulted in the translocation of endotoxin, a major molecule of gut bacteria, from the intestine into blood circulation. In acute uremia with Candida, intestinal injury was more severe due to fungi and the alteration in intestinal bacteria (increased Bacteroides with decreased Firmicutes), leading to the gut translocation of both endotoxin from gut bacteria and (1→3)-β-d-glucan from Candida, which synergistically enhanced systemic inflammation in acute uremia. Both pathogen-associated molecules were delivered to the liver and induced hepatocyte inflammatory responses with a reduced energy production capacity, resulting in acute uremia-induced liver injury. In addition, Lactobacillus rhamnosus attenuated intestinal injury through reduced gut Candida and improved intestinal bacterial conditions.